AN ANALYSIS OF STUDENTS’ RESPONSES TOWARDS THE IMPLEMENTATION OF DIGITAL TEACHING MATERIALS FOR ONLINE LEARNING - Darmayanti, Putu Sri; Lestari, Ni Kadek Herna (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The utility of ICT has been popular yet hasn’t been optimized well enough. However, its existence becomes crucial and compulsory during extreme pandemic, Covid-19. The education fully applies the use of ICT in the learning process as face-to-face meeting is impossible to make. Virtual meeting by online platforms is supported by the digital teaching materials which can be accessed by the students whom have internet connection. This study aimed to figure out the responses of the students towards the implementation of digital teaching materials in online learning. Questionnaire was distributed to the subjects in collecting the data for this qualitative research. The study revealed that the ICT assists the students much in the term of accessible. However, the students need more training on the preparation and following the flow of online learning. Besides, an advanced development of the material is necessary for the provider of the digital materials to engage the students and enhance their understanding.